The Role of Institutional Ownership and Board Diversity To Improve Company performance Using Fixed Effect Method - Ahmad Juliana; Yulianto Denny; Ahmatang Ahmatang; Nurul Hidayat (At-Tadbir : jurnal ilmiah manajemen, 2023)
This study seeks to examine the relationship between board diversity and company performance in tourism sector companies listed on the Indonesia Stock Exchange over the period of 2012-2021. The research also considers the moderating role of institutional ownership in this relationship. The independent variables in this study include board diversity and institutional ownership, while the dependent variable is company performance. The sample of 15 companies was selected using a purposive sampling technique. The data analysis was conducted using panel data regression analysis with the fixed effect model in the STATA MP17 software. The findings of the study indicate a positive impact of board diversity on company performance, and it is observed that the effect of board diversity on company performance is more pronounced when the level of institutional ownership is low.Keywords: Board Diversity, Board of Directors, company performance, governance, Institutional Ownership